Clinical and laboratory characteristics of acute herpes neuroinfections - V.M. Koz'ko (Danylo Halytsky Lviv National Medical University, 2017)
Aim. To determine the clinical and laboratory features of herpes viral neuroinfections, depending on the etiology and severity of the disease.